FEATURES OF PEDAGOGICAL TECHNOLOGY FORMATION OF LITERARY AND LOCAL HISTORY FUTURE PRIMARY TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
The peculiarities of pedagogic technologies of forming of literature-local lore knowledge of future teachers are being considered in the article.